PERFORMANCE OF THE INDIAN MSMES IN THE ERA OF GLOBALISATION - Urvi P. Sheth, Prasanta Chatterjee Biswas (International Journal of Research Science and Management, 2016)
India is a developing nation with scarce capital recourses and widespread unemployment. Small scale industries play a pivotal role in overcoming this problem by their scarce use of capital and more use of labor. Small scale industries play a big role in fighting scarcity of capital in a capital scarce economy like ours. In a labor surplus underdeveloped economy like ours small scale industries are like a boon providing employment to the large scale unemployed. The role of small scale industries is thus even more important in an underdeveloped economy like ours compared to large scale industries. This sector produces as good as 45% of the total manufacturing output and 40% of the total exports. The sector gives employment to about 69 million people in the country. There are over 6000 items ranging from traditional to high tech being manufactured by this country. Small scale sector is said to be providing highest employment after the agriculture sector in the country. The importance of the small scale industries is mainly also because of its contribution to the total industrial production and GDP of India. Looking at the pivotal role that is played by this sector Government has provided protection and support to this sector. In this era of globalization much more of the support and technological help would be welcome step. In India Small Scale Industrial Sector includes Micro, Small and Medium Enterprises.